(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In this article, when we say phoneme variants, we mean such sounds of human speech that we understand that these sounds do not change the meaning of the word, but are heard differently in the pronunciation of some people.